Pemikiran Sayyid Qutb tentang Prinsip Solidaritas dalam Ekonomi Islam - Rahman, Mohammad Taufiq (Hanifiya: Jurnal Studi Agama-Agama, 2021)
This study tries to identify and analyze Islamic thought dealing with the problems of empowering society. This study uses a conceptual analysis, i.e. investigating conceptions or meanings in a concept. By this method, it is found that Islam, represented by Sayyid Qutb, has its own answers to such aforementioned questions.To the problems of empowering society, Qutb states that Islam has no problem in any form of social and economic differences, for Islam has its own system to handle the problem. In Islamic society, all differences are nothing if they are backed by piety. To this, all should have an opportunity to gain the piety. Otherwise, the social system should help those who could not do spiritual things by way of –among others—zakat, charity, and the like.